Visual Resistance and Social Change: Disability Arts as Cultural Intervention in Indonesian Media Landscapes - Yasin, Muhammad; Malizal, Zelynda Zeinab; Rizqi, Putri Umrotur (Psychosocia : Journal of Applied Psychology and Social Psychology, 2024)
This article explores the transformative potential of disability arts in Indonesia by analyzing how inclusive artistic practices challenge dominant media narratives that depict disability through pity, inspiration, or deficit. Employing a comparative qualitative approach, the study integrates discourse analysis of artworks by the Deaf Art Community and Kinanty Andini with media content review and focus group discussions before and after art exposure. The analysis reveals that disability arts foster narrative agency, shifting audience perceptions from stereotypical views to recognition of disabled individuals as empowered and creative agents. Inclusive artworks deploy symbolism, cultural authenticity, and emotional storytelling, enabling participants to engage with disability not as deficiency but as lived, multifaceted identity. Qualitative and quantitative shifts in sentiment evidenced by changes in audience descriptors and thematic coding highlight the potential of art-based interventions to reduce stigma. However, the study also notes limitations, including misinterpretation, co-optation, and inequities in access and representation. Cultural contexts significantly shape the reception of disability narratives, while digital platforms simultaneously democratize and constrain visibility. The study concludes that disability art, while not a panacea, is a critical catalyst for narrative transformation and cultural inclusion. Continued collaboration among artists, scholars, and institutions is necessary to ensure lasting impact and representation.